Monitoring Program Gerdu Kempling Di Kecamatan Banyumanik Kota Semarang Tahun 2013 Atas Pelaksanaan Tahun 2012 - liananto, Rifwan Kukuh; Fathurrohman, Fathurrohman; Marom, Aufarul (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Gerdu kempling is aninnovation, created from condition and problems in the Semarang City. The purpose of the program in 2012 is to reduce the number of poor people in the Semarang City of 2% per year, or as much as 3.473 families in 48 sub –district. His research aims to know the implementation of the program in 2012 and how his achievments. This research was analyzed with a model monitoring Peter Rossi and using qualitative research type. This study used a qualitative descriptive research type. Research findings obtained by interviewing the actors involved in the program, namely the city of Semarang government, NGOs, the poor and the community. Researchers also spread a questionnaire to determine the level of satisfaction of the poor against Kempling Gerdu program. From the results of the analysis are used, namely the analysis of the performance of government agencies, it can be concluded that the government of Semarang city has successfully reached the target program in 2012 that has been determined. Poor people are quite satisfied with the program activities Gerdu Kempling received. The program succeeded in empowering the poor and increase revenue independently. Good cooperation between the government and the various stakeholders is one of the success factors. Through performance measurements using the evaluation form, the program achieved success by 73.64%